Co-design of an online teacher training program tailored for rural Japanese teachers to deliver neuroscience-informed mental health interventions to children - Yu Takizawa; Matthew Bambling; Hsien-Jin Teoh; Sisira Edirippulige (Quality Education for All)
Purpose – This study aims to co-design a new online teacher training program tailored for rural Japanese teachers to deliver neuroscience-informed mental health interventions to children. The objective was to reduce the educational gap between Japanese teachers in rural and urban areas, effectively improving children’s mental health. Design/methodology/approach – The online teacher training program was developed by incorporating insights gathered from teacher interviews in the authors’ needs-analysis study. Feedback from experts in neuroscience, clinical psychology, educational psychology, education and Japanese culture was integrated. A focus group was held to gauge the suitability of content and formats, building on input from a selection of five primary school teachers out of the 20 who participated in the authors’ research on needs-analysis. Findings – The focus group findings supported the suitability of co-designed online training program, indicating that its content and format are mostly suited for Japanese educators in rural areas to acquire knowledge of neuroscience-informed mental health interventions. However, revisions were proposed, including the inclusion of more detailed intervention guidelines and the provision of worksheets for classroom utilization. These suggestions were integrated to revise the online teacher training program. Future research could investigate the impact of program on improving the mental health of Japanese children. Originality/value – To the best of the authors’ knowledge, this study represents the first attempt to report on the co-design of an online teacher training program that incorporated opinions from Japanese primary school teachers in rural areas, aiming to close the educational gap among Japanese teachers. It was designed to train teachers in providing neuroscience-informed mental health interventions.